Indigenizing the (final) frontier: the art of Indigenous storytelling through graphic novels. Issue 2 (4th May 2019) - Tiger, Yvonne N.
Abstract : When Indigenous artists and writers entered the graphic novel genre, they opened up the world of ancient tribal tales, traditions, and customs to a new generation of readers, thus allowing the past to relay important cultural knowledge to our youth while Indigenizing a Western-dominated art form. In this paper, I seek to contribute to the dialogue about Indigenous concepts of space, time, and the oral tradition, to include present and future iterations of our knowledge systems in Indigenous sci-fi and speculative storytelling graphic novels. I contend that Indigenous artists are reimagining an older pictorial tradition that relayed cultural ways of knowing the stars and the universe to our youth, and charting new ways forward by connecting the past to present in the process. These specific genres 'retell' and 're-understand' traditional narratives with culturally grounded speculation about Indigenous futures and space, revealing a persistent cultural continuity that is deeply connected to our traditional terrains in fluid and exciting forms of artistic expression. I argue that Indigenous science fiction can, and does, critique and resist the continuation of settler-colonial endeavors by exploring and re-indigenizing a space that we have always been connected to, but is also customarily part of the settler frontier narrative in this genre.